X/Y translocation in a family with Leri-Weill dyschondrosteosis - Calabrese, Gaetano; Fischetto, Rita; Stuppia, Liborio; Capodiferro, Francesca; Mingarelli, Rita.; Causio, Franco; Rocchi, Mariano; Rappold, Gudrun; Palka, Giandomenico (Human genetics, 1999)
An X/Y translocation associated with Leri-Weill dyschondrosteosis (LWD) was detected in a boy and in his mother. FISH analysis with specific probes for SHOX and SRY displayed no signal on the der(X), while one signal for SHOX was detected on the normal X chromosome in the mother, and one signal each for SHOX and SRY was detected on the normal Y chromosome in the proband.